Versorgungszufriedenheit und Konsumverhalten.: Bedeutung subjektiver Einstellungen für die Einkaufsorientierungen - Kagermeier, Andreas (ERDKUNDE, 1991)
This article focuses on the question of which part different models play in explaining shopping orientations within a system of competing central places with different levels of retailing facilities. The influence of three different groups of variables on shopping activities was considered: (1) socio-demographic attributes; (2) the two variables which are used in econometric gravity-models, the size of retailing facilities, and the distance from the consumer’s residence; (3) subjective attitudes towards an object (following the adequacy-importance model). The comparison of those three models showed that among them the impact of attitudes on consumer behavior is the most reliable far explaining consumer behavior. Although at the moment the inter-relationship between the attitudes and the shopping orientations is still not reliable enough and needs improvement, this model would deserve to be mare widely spread and further developed within geography.